Study on Thermal/Moisture Expansion Stress of a Drop-Out Fuse Insulator - Jun Li; Suhui Zhang; Jinpeng Xie; Fei Jiang; Zhaoyu Zhang; Guangru Zhang (Journal of Applied Science and Engineering, 2025)
Drop-out fuses are widely used electrical devices, and their reliability directly affects the safety of power supply systems. Porcelain insulators, as a critical component, are prone to cracking, which significantly disrupts the order of power production. Therefore, starting from the perspective of stresses caused by mechanical external forces, environmental temperature changes, and moisture-induced expansion of cement adhesive, the stress distribution of porcelain insulators is analyzed to determine the causes of failure. The study reveals that the maximum stress induced by environmental temperature rise occurs at the contact interface between the adhesive hole in the middle of the insulator and the cement adhesive. When the temperature rises by 50 K, the porcelain insulator still maintains relatively good strength. However, the cement adhesive is subjected to significant shear stress, resulting in a failure zone near the adhesive hole. Consequently, the damage to the cement adhesive caused by temperature rise is identified as the primary reason for the failure of drop-out fuses. Additionally, the stress caused by moisture-induced expansion of the cement adhesive cannot be ignored. When the relative water absorption of the cement adhesive exceeds 90.3%, the compressive stress acting on it surpasses its allowable stress, leading to failure. Therefore, controlling the water absorption rate of the cement adhesive and delaying the ingress of moisture are critical measures to enhance the operational reliability of porcelain insulators.